A continuous merging method for natural surface elements based on morphing - Yue Chen; Haizhong Qian (Geocarto International)
Electronic maps urgently require continuous scale representation, with element merging being the core part. However, current research on the continuous merging of natural areal elements focuses on the selection of merging objects, neglecting the crucial aspect of shape reconstruction. Additionally, due to the complexity and diversity of natural element boundaries, traditional algorithms designed for artificial areal elements with rectangular characteristics are no longer effective. Therefore, this study proposed a continuous merging method for natural areal elements that takes into account both element selection and shape reconstruction. Initially, the correspondence between elements in the initial and final maps is established. Then, element merging is conducted based on the Greiner-Hormann algorithm. Subsequently, the correspondence between boundary lines and the final scale map is determined. Boundary lines with established correspondences are simplified using Morphing technology, while non-corresponding lines are simplified through Bend group partitioning. Experiments conducted on lake and island data demonstrate that the proposed method can produce reasonable and smoothly continuous merging effects, with boundaries progressively simplifying as the scale decreases.